Fungsi Pengawasan Komisi D Terhadap Pelaksanaan Perda Tentang Penyelenggaraan Pendidikan di Kabupaten Ciamis - Ai Nurmalasari; Mico Ariel Wahyu Purnomo; Muhammad Sultan; Regi Refian Garis (Public Administration Dept, Faculty of Social and Political Science, 2024)
This research discusses the implementation of the supervisory function of Commission D towards the local regulation (perda) on education management in Ciamis Regency. According to Feriyanto and Triayana (2005:65), the supervision process involves several steps. First, establishing standards as a reference. Next, determining the measurement of activity implementation. Then, comparing the actual implementation with the established standards and analyzing any possible deviations. Finally, taking actions to address the issues detected during the supervision process. The main problem addressed in this research is how the supervisory function of Commission D influences the implementation of the local regulation on education management in Ciamis Regency. The method used is a qualitative descriptive approach with data collected through literature studies, field surveys, observations, and interviews. The results of the research show that the supervision conducted by Commission D in Ciamis Regency is not yet optimal, mainly due to the lack of coordination between Commission D and the education department regarding the implementation of the local regulation on education management in Ciamis Regency.